Diabetes Mellitus Diagnosed in Childhood and Adolescence With Negative Autoimmunity: Results of Genetic Investigation - Lezzi, Marilea; Aloi, Concetta; Salina, Alessandro; Fragola, Martina; Bassi, Marta; Strati, Marina Francesca; d’Annunzio, Giuseppe; Minuto, Nicola; Maghnie, Mohamad (Frontiers in Endocrinology, 2022)
Monogenic diabetes is a rare form of diabetes, accounting for approximately 1% to 6% of pediatric diabetes patients. Some types of monogenic diabetes can be misdiagnosed as type 1 diabetes in children or adolescents because of similar clinical features. Identification of the correct etiology of diabetes is crucial for clinical, therapeutic, and prognostic issues. Our main objective was to determine the prevalence of monogenic diabetes in patients with diabetes mellitus, diagnosed in childhood or in adolescence, and negative autoimmunity. We retrospectively analyzed clinical data of 275 patients diagnosed with insulin-dependent diabetes at age <18yr in the last 10 years. 8.4% of subjects has negative autoimmunity. Their DNA was sequenced by NGS custom panel composed by 45 candidate genes involved in glucose metabolism disorder. Two novel heterozygous pathogenic or likely pathogenic variants (10,5% of autoantibody negative subjects) were detected: the frameshift variant c.617_618insA in NEUROD1 exon 2 and the missense change c.116T>C in INS exon 2. Our study corroborates previous results of other reports in literature. NGS assays are useful methods for a correct diagnosis of monogenic diabetes, even of rarest forms, highlighting mechanisms of pediatric diabetes pathogenesis.